Writers of Indian diaspora : theory and practice - Jain, Jasbir (Jaipur : Rawat Publications, 1998)
Contributory essays; some presented at a seminar held in December 1996 at the University of Rajasthan.
Includes bibliographical references.
Keywords: INDIC LITERATURE (ENGLISH) -- 20th CENTURY -- HISTORY AND CRITICISM